Psocidae (Insecta: Psocoptera) from the Islands of Bali and Lombok, Indonesia - Endang Sri Kentjonowati; Ian W. B. Thornton (BRIN Publishing (Penerbit BRIN), 1992)
Collection of Psocidae in Bali und Lombok in August-December 1987 by I.W.B.T., in September 198'1 by C. Lienhard, and in August 1990 by E.S.K. were examined to characterise taxonomically this family on these islands. Thirteen species of the family had previously been reported on one or both islands. Species in the collections under study not previously recorded from the islands are: Ptycta incurvata Thornton (known from Hong Kong); Trichadenotecnum malayense New (known from the Malay Peninsula); Cycetes thyrsophoroides Enderlein (known from Java)two species (representing a new genus, Indoblaste); and seven other newly described species, one each of Sigmatoneura and Ptycta, three of Psocidus s.str. and two of Trichadenotecnum. Moreover, two species, one psocine and one amphigerontine could not be placed into presently diagnosed genera and may represent new genera. Descriptions of previously undescribed species are provided, as are descriptions ofthe males of Clematoscenea lemniscata Enderlein, Psocidus reidi Thomton, and a further description of Cycetes thyrsophoroides. Ptycta frontalis Thornton. A key to genera, and keys to species within larger genera, are provided, using, where possible, features observable without dissection. Five species from Bali are endemic, and 5 from Lombok; both islands share a further 7 species endemic to the two islands. Additionally, 10 species known from the islands are found elsewhere. The Bali-Lombok fauna of Psocidae now stands at 27 species and there is no evidence from the species discovery curve that the total fauna has yet been sampled. Of the 10 single-island endemics none is eurytopic (found at a wide range of altitudes). In contrast, of the 11 species found on both islands, 8 (73%) are eurytopic. Bali endemics tend to be highland stenotopes (on present evidence) whereas Lombok endemics tend to be restricted to middle, elevations. Of the ten species known from elsewhere, only two are known from east of Lombok (from Komodo). The others are from the Malay Peninsula, Singapore, Sumatra, Java, Madura, and Hong Kong.